THE IMPACT OF PARENTING PATTERNS ON THE ACHIEVEMENT OF STUDENTS OF THE FACULTY OF ISLAMIC RELIGION - Zamza Ramadhani Miftakhul Jannah; Triono Ali Mustofa (ITB AAS Indonesia Surakarta, 2024)
Getting good learning is a very meaningful part in giving birth to a generation that is ready to take over the task of building the future from the previous generation. Learning achievement is the result achieved by children in understanding tasks or topics obtained within a certain period of time. Learning is everyone's duty. The purpose of this research is to examine whether the results obtained are the same as previous studies. So, the researcher is interested in further research about